CLINICAL OUTCOME AND SEVERITY OF CLOSTRIDIOIDES (CLOSTRIDIUM) DIFFICILE INFECTION AT A TERTIARY REFERRAL HOSPITAL IN BRAZIL - Fernando Antônio Castro CARVALHO; Rodrigo Otávio Silveira SILVA; Bárbara Moreira Ribeiro Trindade dos SANTOS; Amanda Nádia DINIZ; Eduardo Garcia VILELA (Arquivos de Gastroenterologia, 2023)
ABSTRACT Background: Clostridioides difficile infection (CDI) is a potentially severe disease that can present with refractoriness, recurrence, and evolution to death. In Brazil, the epidemiology of CDI seems to differ from that of the United States and most European countries, with only one ribotype (RT) 027-related case and a high prevalence of RT106. Objective: The aim of this study was to evaluate the outcomes of CDI and its possible association with ribotypes at a university hospital in Brazil. Methods: A total of 65 patients with CDI were included and stool samples were submitted to A/B toxin detection and toxigenic culture, and toxigenic isolates (n=44) were also PCR ribotyped. Results: Patients’ median age was 59 (20-87) years and there were 16 (24.6%) deaths. The median Charlson comorbidity index (CCI) was 4 (0-15) and 16.9% of the patients had CCI ≥8. The ATLAS score and non-improvement of diarrhea were related to higher mortality. A longer length of hospitalization was related to the enteral nutrition and use of multiple antibiotics. The period between CDI diagnosis and hospital discharge was longer in those who received new antibiotics after diagnosis, multiple antibiotics, and required intensive care treatment. Recurrence was associated with CCI >7. Twenty ribotypes were identified and RT106 was the most frequently detected strain (43.2%). No relationship was observed between the ribotypes and outcomes. CDI was present in patients with more comorbidities. Conclusion: Risk factors for higher mortality, longer hospital stay and recurrence were identified. A diversity of ribotypes was observed and C. difficile strains were not related to the outcomes.